Nitrogen-doped carbon material and preparation method and application thereof
The preparation of nitrogen-doped carbon materials through a hydrothermal process enhances the specific surface area and pore structure, addressing the challenge of high energy density in supercapacitors, achieving a 40% increase in capacity and energy density while reducing size and cost.
Patent Information
- Application Number
- CN202411349426.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-27
AI Technical Summary
Existing supercapacitors face challenges in achieving high energy density without increasing volume and weight, leading to large size and high production costs, and existing methods for improving energy density involve complex processes and expensive materials.
A method for preparing nitrogen-doped carbon materials using a hydrothermal process and activator activation, incorporating trans-1,2-cyclohexanediaminetetraacetic acid (CDTA) as a nitrogen source, to enhance the specific surface area and pore structure, resulting in a three-dimensional porous carbon material.
The nitrogen-doped carbon materials increase the capacity and energy density of supercapacitors by at least 40% while reducing their size, using cost-effective activated carbon and simplifying the manufacturing process, thus expanding their application scenarios.
Smart Images

Figure CN119208025A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to the technical field of supercapacitor electrode materials, and in particular, to a nitrogen-doped carbon material and a preparation method and application thereof. Background Art
[0002] With the continuous growth of global energy demand and the increasingly serious environmental problems, the storage and utilization of electric energy has become a very practical research direction. Supercapacitors, as an electronic component that physically stores energy through electrostatic adsorption, have the advantages of high power density, long life, high safety, and green environmental protection. Compared with traditional capacitors, they have higher energy density, and compared with lithium batteries, they have a wider operating temperature and greater power density. It is a new type of energy storage electronic component between lithium batteries and traditional capacitors, and has broad application prospects in electric vehicles, renewable energy, rail transportation and other fields.
[0003] Due to the low energy density of supercapacitors, in some high-power consumption application scenarios, such as rail transit, photovoltaic energy storage, and intelligent industrial control, it is necessary to use supercapacitor monomers in series and parallel to achieve the required energy. However, large modules composed of series and parallel connections have disadvantages such as large size and high production costs, which leads to certain resistance to supercapacitors in high-power consumption application scenarios. Therefore, how to improve the unit energy density of supercapacitors without increasing the volume and weight of supercapacitors is currently a hot research direction in the industry.
[0004] According to the energy calculation formula of supercapacitor E = 1 / 2CV 2 It can be seen that the energy density of supercapacitors is mainly related to the capacity and working voltage of the product, so researchers in the industry mainly increase the capacity or working voltage of the product to achieve the purpose of increasing the energy density of the product. For example, patent CN202011287210.5 improves the working voltage (4.7V) of the product by modifying the electrolyte to achieve the purpose of increasing the energy density of the product; patent CN202311225848.X selects MXenes materials with higher specific capacity and modifies them to further increase the specific capacity of the material, thereby achieving the purpose of increasing the energy density of the product.
[0005] The above methods for improving the energy density of supercapacitors have the problems of complex manufacturing process, high requirements on the preparation environment, expensive raw materials used, and being not conducive to industrial promotion. Therefore, there is an urgent need for a supercapacitor manufacturing technology with low production cost, simple production process, and effective improvement of the energy density of supercapacitors. Summary of the invention
[0006] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a nitrogen-doped carbon material and a preparation method and application thereof.
[0007] To achieve the above object, the technical solution adopted by the present invention is: the present disclosure provides a method for preparing a nitrogen-doped carbon material, comprising the following steps:
[0008] Adding activated carbon and a nitrogen source to a solvent and mixing them evenly to obtain a first solution; placing the first solution in a reaction kettle and performing a hydrothermal reaction to obtain a first product;
[0009] The first product and an activator are mixed and activated to obtain a nitrogen-doped carbon material;
[0010] The nitrogen source is trans-1,2-cyclohexanediaminetetraacetic acid (CDTA).
[0011] In one embodiment, the mass ratio of the activated carbon to the nitrogen source is 1-4.
[0012] In one embodiment, the mass ratio of the first product to the activator is 1-4.
[0013] In one embodiment, the hydrothermal reaction is carried out at a temperature of 160-200° C. and for a time of 20-30 h.
[0014] In one embodiment, the activation temperature is 600-800° C. and the activation time is 1.5-3 h.
[0015] In one embodiment, the activator is at least one of sodium hydroxide, potassium hydroxide, sodium oxide, potassium oxide, sodium carbonate, potassium carbonate, potassium bicarbonate, sodium bicarbonate, and calcium oxide.
[0016] On the other hand, the present disclosure provides a nitrogen-doped carbon material, which is prepared by the above-mentioned method for preparing the nitrogen-doped carbon material.
[0017] In yet another aspect, the present disclosure provides an electrode sheet including a nitrogen-doped carbon material, a conductive agent, and a binder.
[0018] In one embodiment, the conductive agent is at least one of conductive carbon black, carbon nanotubes, graphene, and vapor-grown carbon fibers.
[0019] In one embodiment, the binder is at least one of N-methylpyrrolidone, sodium carboxymethyl cellulose, and styrene-butadiene rubber.
[0020] On the other hand, the present disclosure also provides a supercapacitor comprising the above-mentioned electrode sheet.
[0021] Compared with the prior art, the present invention has the following beneficial effects:
[0022] 1. The present invention adopts a hydrothermal method and an activator activation method to perform nitrogen atom doping modification on carbon materials, so that the obtained nitrogen-doped carbon materials have a more complete three-dimensional pore structure, and the specific surface area and active sites of the nitrogen-doped materials are improved. Secondly, nitrogen and carbon elements are in adjacent positions in the periodic table, and the atomic radius of nitrogen atoms (N) and C atoms are close, so C atoms in the atomic lattice of carbon materials are more easily replaced during the doping process, thereby improving the stability of nitrogen-doped materials; thirdly, nitrogen atoms have a higher electron cloud density, and doping nitrogen elements in carbon materials can effectively improve the conductivity of nitrogen-doped carbon materials; nitrogen-doped carbon materials are used in supercapacitors, and under the condition of the same size, the capacity and energy density of supercapacitors are increased by at least 40%, which can effectively reduce the size of supercapacitors required in high power consumption fields, greatly expanding the application scenarios of supercapacitors.
[0023] 2. The nitrogen-doped carbon material disclosed in the present invention has fewer doping elements. Compared with multi-element doping, the specific surface area and electrical conductivity of the nitrogen-doped carbon material can be increased while reducing the types of doping elements and simplifying the process, thereby improving the capacitance performance of the supercapacitor.
[0024] 3. Existing methods for improving the energy density of supercapacitors usually involve modifying the electrolyte or selecting expensive raw materials such as MXenes materials, carbon nanotubes, graphene, etc. The raw materials used in such methods are more expensive than activated carbon, and the manufacturing process has high environmental requirements (a water-free environment is required). They are only suitable for laboratory preparation and are not conducive to commercial promotion. The raw materials used in the supercapacitor disclosed in the present invention are relatively low-cost activated carbon materials, which have no special requirements for the preparation environment, are green and environmentally friendly, have commercial promotion value, and can truly expand the application scope of supercapacitors on a large scale. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 The scanning electron microscope images of Examples 1-3 and Comparative Examples 1-3 are shown;
[0026] Figure 2 It is the N2 adsorption / desorption isotherm diagram of Examples 1-3 and Comparative Example 1;
[0027] Figure 3 It is the BJH pore size distribution diagram of Examples 1-3 and Comparative Example 1;
[0028] Figure 4 This is a test diagram of the actual capacity of supercapacitor products prepared using the carbon materials of Examples 1-3 and Comparative Examples 1-3;
[0029] Figure 5 This is a test chart of the actual internal resistance of supercapacitor products prepared using the carbon materials of Examples 1-3 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0030] For this specific embodiment, it should be understood that, unless explicitly indicated to the contrary, the present disclosure may assume alternative variations and step sequences. In addition, except in any operating examples or otherwise indicated, all numerals used to express the amount of, for example, ingredients in the specification and claims should be understood to be modified by the term "about" in all cases. Therefore, unless otherwise indicated, the numerical parameters set forth in the following specification and the appended claims are approximate values, which can vary according to the desired properties to be obtained by the present disclosure. At least, and without attempting to limit the scope of the application of the doctrine of equivalents to the claims, each numerical parameter should at least be interpreted according to the number of reported significant figures and by applying ordinary rounding techniques.
[0031] Although the numerical ranges and parameters setting forth the broad scope of the present disclosure are approximations, the numerical values set forth in the specific examples are reported as precisely as possible. Any numerical value, however, inherently contains certain errors necessarily resulting from the standard deviation found in their respective testing measurements.
[0032] In addition, it should be understood that any numerical range cited herein is intended to include all sub-ranges included therein. For example, a range of "1 to 10" is intended to include all sub-ranges between the recited minimum value 1 (inclusive) and the recited maximum value 10 (inclusive), i.e., the minimum value is equal to or greater than 1 and the maximum value is equal to or less than 10.
[0033] As used herein, “including,” “comprising,” and similar terms should be understood as being synonymous with “comprising,” and thus are open-ended and do not exclude additional undescribed or unrecited elements, materials, components, or method steps in the context of this application.
[0034] As used herein, "consisting of is to be understood in the context of this application as excluding the presence of any unspecified elements, ingredients or method steps.
[0035] As used herein, "consisting essentially of" is understood in the context of this application to include the specified elements, materials, ingredients, or method steps "as well as those that do not materially affect the basic and novel characteristics of what is described." As used herein, open-ended terms include closed terms, such as "consisting essentially of" and "consisting of."
[0036] In this application, unless specifically stated otherwise, the use of the singular includes the plural and the plural encompasses the singular. For example, although "a" nitrogen source is mentioned herein, combinations (ie, a plurality) of these components may be used.
[0037] Additionally, in this application, the use of "or" means "and / or" unless specifically stated otherwise, although "and / or" may be explicitly used in some cases.
[0038] As used herein, unless otherwise stated, the term "substantially free" means that the specific material is not intentionally added to the mixture or composition, respectively, and is present only as an impurity in trace amounts of less than 5 wt % based on the total weight of the mixture or composition, respectively. As used herein, unless otherwise stated, the term "substantially free" means that the specific material is present only in an amount of less than 2 wt % based on the total weight of the mixture or composition, respectively. As used herein, unless otherwise stated, the term "completely free" means that the mixture or composition, respectively, does not include the specific material, i.e., the mixture or composition includes 0 wt % of such material.
[0039] In order to solve the problem that the size and unit energy density of supercapacitors in the prior art cannot be balanced.
[0040] The present disclosure provides a method for preparing a nitrogen-doped carbon material, comprising the following steps:
[0041] Adding activated carbon and a nitrogen source to a solvent and mixing them evenly to obtain a first solution; placing the first solution in a reaction kettle and performing a hydrothermal reaction to obtain a first product;
[0042] The first product and an activator are mixed and activated to obtain a nitrogen-doped carbon material;
[0043] The nitrogen source is trans-1,2-cyclohexanediaminetetraacetic acid (CDTA).
[0044] The present invention adopts a hydrothermal method and an activator activation method to modify the carbon material by nitrogen atom doping, thereby increasing the specific surface area of the activated carbon and improving the pore structure of the activated carbon, and obtaining a three-dimensional graded porous nitrogen-doped carbon material including micropores (pore diameter less than 2nm), mesopores (pore diameter greater than or equal to 2nm and less than or equal to 50nm), and macropores (pore diameter greater than 50nm). A mixture of the nitrogen-doped carbon material, a conductive agent, and a binder is formed into an electrode sheet of a supercapacitor. Under the condition that the size of the supercapacitor is the same, the capacity and energy density of the supercapacitor are increased by at least 40%, which can effectively reduce the size of the supercapacitor required in the high power consumption field, and greatly expand the application scenarios of the supercapacitor.
[0045] In one embodiment, the mass ratio of the activated carbon to the nitrogen source is 1-4, for example, but not limited to 1, 1.3, 1.5, 1.8, 2, 2.2, 2.5, 2.7, 3.3, 3.5, 3.8, 4.
[0046] In the present disclosure, the mass ratio of activated carbon and nitrogen source will affect the specific surface area and pore structure of the nitrogen-doped carbon material. If the mass of the nitrogen source is too small, the specific surface area of the obtained nitrogen-doped carbon material will be small and the pore size will be small; if the mass of the nitrogen source is too large, the specific surface area of the obtained nitrogen-doped carbon material will decrease and the pore size will be too large, thereby destroying the three-dimensional structure of the nitrogen-doped carbon material.
[0047] Specifically, after the hydrothermal reaction is completed, the obtained product needs to be washed, solid-liquid separated and dried to obtain the first product. Specifically, the washing solvent and the number of times are not limited, and the washing liquid can be used for clarification, and the washing solvent and the number of times can be adjusted according to the situation.
[0048] Specifically, after activation, the obtained product needs to be washed, solid-liquid separated and dried to obtain nitrogen-doped carbon material. Specifically, the washing solvent and the number of times are not limited, as long as the pH of the washing liquid is neutral, and the washing solvent and the number of times can be adjusted according to the situation. Preferably, the obtained washing solvent is a hydrochloric acid solution, which can react with the activator to remove excess activator and other unreacted impurities, while shortening the number and time of washing.
[0049] In the present disclosure, there is no specific limitation on the method of solid-liquid separation. For example, solid-liquid separation can be performed by centrifugal separation or filtration separation.
[0050] In the present disclosure, the drying method and equipment are not specifically limited; for example, any one of an oven, a box furnace, and a double-cone dryer can be used for drying.
[0051] In one embodiment, the method of mixing the first product and the activator is not specifically limited, as long as the first product and the activator can be mixed evenly; for example, the first product and the activator can be mixed by the following steps: the specific steps are: adding the first product and the activator to water, stirring evenly to obtain a mixed solution, and drying the mixed solution to obtain a mixture of the first product and the activator.
[0052] In one embodiment, the activator is at least one of sodium hydroxide, potassium hydroxide, sodium oxide, potassium oxide, sodium carbonate, potassium carbonate, potassium bicarbonate, sodium bicarbonate, and calcium oxide.
[0053] On the other hand, the present disclosure provides a nitrogen-doped carbon material, which is prepared by the above-mentioned method for preparing the nitrogen-doped carbon material.
[0054] In yet another aspect, the present disclosure provides an electrode sheet including a nitrogen-doped carbon material, a conductive agent, and a binder.
[0055] In some embodiments, the present disclosure does not have any special limitation on the conductive agent, and any conductive agent known in the art can be used. The conductive agent can be but is not limited to conductive carbon black, carbon nanotubes, graphene, and vapor-grown carbon fiber. In the present disclosure, the content of the conductive agent is 3-6 parts based on 100 parts of the total mass of the electrode sheet.
[0056] In some embodiments, the present disclosure does not have any special limitation on the binder, and a binder well known in the art can be used. The binder can be but is not limited to N-methylpyrrolidone, sodium carboxymethyl cellulose, and styrene-butadiene rubber. In the present disclosure, the content of the binder is 2-3 parts based on 100 parts of the total mass of the electrode sheet.
[0057] On the other hand, the present disclosure also provides a supercapacitor comprising the above-mentioned electrode sheet.
[0058] The embodiment of the present application also provides a supercapacitor, including a positive electrode sheet, a negative electrode sheet, and a separator between the positive electrode sheet and the negative electrode sheet, and also includes an electrolyte filling the ultra-micropores between the positive electrode sheet and the separator and between the negative electrode sheet and the separator. The negative electrode sheet includes a negative electrode collector and a negative electrode material distributed on the negative electrode collector, wherein the positive electrode sheet includes a positive electrode collector and a positive electrode material distributed on the positive electrode collector, and both the positive electrode material and the negative electrode material can be the nitrogen-doped carbon material prepared in the present application.
[0059] In some embodiments, the electrolyte is an organic electrolyte salt, specifically at least one of ethylene carbonate, propylene carbonate, and acetonitrile.
[0060] In some embodiments, the present application does not have any special limitation on the separator, and any separator known in the art can be used. The separator can be, but is not limited to, a polyethylene film, a polypropylene film, a cellulose film, or a modified polymer thereof.
[0061] In some embodiments, the present application has no special requirements on the preparation method of the supercapacitor, and the supercapacitor can be prepared by methods well known in the art, and can be a symmetrical capacitor or an asymmetrical capacitor.
[0062] The following is a further description of the embodiments of the present application in multiple embodiments. The embodiments of the present application are not limited to the following specific embodiments. Within the scope of the unchanged main rights, appropriate changes can be made to the implementation.
[0063] Example 1
[0064] This embodiment provides a method for preparing a nitrogen-doped carbon material, comprising the following steps:
[0065] (1) 800 g of activated carbon and 200 g of CDTA were added to 1600 mL of deionized water and mixed evenly to obtain a first mixed solution. The first mixed solution was placed in a reactor and heated to 180° C. at a heating rate of 3° C. / min for hydrothermal reaction. The mixture was kept warm for 24 h and cooled. The obtained product was washed with anhydrous ethanol and deionized water in turn until the filtrate was clear. The obtained filtrate was dried in a 60° C. forced air drying oven for 24 h to obtain a first product.
[0066] (2) adding 1000 g of the first product and 500 g of KOH into 600 mL of deionized water and mixing them evenly to obtain a second solution, and drying the second solution in a forced air drying oven at 80° C. to obtain a mixture of the first product and KOH, referred to as the second product;
[0067] (3) The second product was activated by heating to 700°C at a heating rate of 3°C / min under a nitrogen protective atmosphere, kept warm for 2 hours, and cooled to room temperature. The obtained product was washed with 0.2 mol / L HCl solution until the pH of the filtrate was 7±0.2. The obtained filtrate was dried in a forced air drying oven at 80°C for 24 hours and ground to obtain a nitrogen-doped carbon material, which was labeled as NPC-1.
[0068] Example 2
[0069] This embodiment provides a method for preparing a nitrogen-doped carbon material, which differs from Embodiment 1 only in that the mass of CDTA in step (1) is 400 g, and the remaining steps and parameters are the same as those in Embodiment 1. The nitrogen-doped carbon material obtained in Embodiment 2 is marked as NPC-2.
[0070] Example 3
[0071] This embodiment provides a method for preparing a nitrogen-doped carbon material, which differs from Example 1 only in that the mass of CDTA in step (1) is 600 g, and the remaining steps and parameters are the same as those in Example 1. The nitrogen-doped carbon material obtained in Example 3 is marked as NPC-3.
[0072] Example 4
[0073] This embodiment provides a method for preparing a nitrogen-doped carbon material, which differs from Embodiment 1 only in that the mass of CDTA in step (1) is 800 g, and the remaining steps and parameters are the same as those in Embodiment 1.
[0074] Comparative Example 1
[0075] The carbon material was not subjected to any treatment and was labeled as NPC-0.
[0076] Comparative Example 2
[0077] This comparative example provides a method for preparing a nitrogen-doped carbon material, which differs from Example 2 only in that urea is used to replace CDTA, and the remaining steps and parameters are the same as those in Example 2, and is marked as NPC-4.
[0078] Comparative Example 3
[0079] This comparative example provides a method for preparing a nitrogen-doped carbon material, which differs from Example 2 only in that glucosamine is used to replace CDTA, and the remaining steps and parameters are the same as those in Example 2, and is marked as NPC-5.
[0080] Performance Testing
[0081] (1) Use scanning electron microscope to test SEM photos.
[0082] (2) The prepared carbon materials were characterized by nitrogen adsorption at 77.3K using the Autosorb iQ2 physical adsorption instrument. The specific surface areas and pore size distributions of materials NPC-0, NPC-1, NPC-2, NPC-3, NPC-4, and NPC-5 were analyzed using the DFT method.
[0083] (3) Using a stacked dual-electrode system to evaluate the capacitance performance of the supercapacitor of the present application. The specific steps are as follows:
[0084] Accurately weigh 380 g of nitrogen-doped carbon material, 46 g of conductive carbon, 7.8 g of sodium carboxymethyl cellulose, 20 g of styrene-butadiene rubber, 14 g of N-methylpyrrolidone and 710 g of deionized water, and stir to form a slurry;
[0085] The slurry was coated on the corroded aluminum foil to make a double-sided electrode sheet with a thickness of 212±1μm and a surface density of 0.0168g / cm 2 ; The obtained double-sided electrode sheet is rolled to obtain a double-sided electrode sheet with a thickness of 183±1μm; cut to obtain a positive electrode sheet with a width of 18mm and a length of 83mm, and a negative electrode sheet with a width of 18mm and a length of 71mm;
[0086] The above-mentioned positive electrode sheet, negative electrode sheet and separator with a width of 20.5 mm were made into battery cells by winding, and the obtained battery cells were subjected to multi-stage vacuum baking, and then fully automated impregnation sealing was carried out under dry conditions with a dew point temperature of -60°C to form supercapacitor cells, which were tested on an electrochemical workstation.
[0087] Capacity test method: Use a charge and discharge tester to test the capacity, the constant current charge and discharge current is 157mA, the constant current charge voltage is 2.7V, and the constant current discharge cut-off voltage is 0.2V;
[0088] Internal resistance test method: Use internal resistance tester to test internal resistance.
[0089] The test results are shown in Table 1.
[0090] Table 1 Test results of specific surface area, pore size distribution and capacitance performance of each embodiment and comparative example
[0091] Specific surface area capacity Internal resistance Example 1 <![CDATA[1348.5g / m 2 ]]> 6.62F 66.31mΩ Example 2 <![CDATA[1956.8g / m 2 ]]> 7.29F 46.52mΩ Example 3 <![CDATA[1745.3g / m 2 ]]> 7.18F 56.28mΩ Comparative Example 1 <![CDATA[1100.2g / m 2 ]]> 5.22F 75.62mΩ Comparative Example 2 <![CDATA[1228.4g / m 2 ]]> 6.21F 70.54mΩ Comparative Example 3 <![CDATA[1091.3g / m 2 ]]> 5.13F 80.12mΩ
[0092] Figure 1 The scanning electron microscope images of Examples 1-3 and Comparative Examples 1-3 are shown in FIG. Figure 1 ac are respectively embodiments 1, 2, and 3, Figure 1 df are comparative examples 1, 2, and 3 respectively; Figure 1 As can be seen in Figure d, when CDTA is not added as a structure-directing agent, the sample surface is smooth and no pore structure is formed. Due to the different amounts of CDTA added to the sample, the pore structure and quantity generated on the sample surface are also different (Figures a, b and c). Only a small number of micropores are formed on the sample surface ( Figure 1 a), while there are a large number of micropores in Figures b and c. This is in sharp contrast to the microscopic morphology of the material when CDTA is not added, indicating that the introduction of CDTA is conducive to the formation of the pore structure of the sample. As can be seen from Figure b, when the mass ratio of activated carbon to CDTA is 2:1, it is mixed with KOH and activated at high temperature to obtain a porous carbon material with a good three-dimensional structure. As shown in Figure c, when the mass ratio of activated carbon to CDTA is 4:3, the structure of the carbon material collapses and a good three-dimensional structure cannot be formed. The amount of CDTA will directly affect the microscopic morphology of the carbon material, and the morphological structure is optimal when the mass percentage is 2:1.
[0093] Depend on Figure 1 e and Figure 1 It can be seen from f that the nitrogen-doped carbon material prepared using urea and glucosamine as nitrogen sources has an obvious structural collapse and does not form a good three-dimensional pore structure. In comparison, using CDTA as a nitrogen source has obvious advantages.
[0094] Figure 2 It is the N2 adsorption / desorption isotherm diagram of Examples 1-3 and Comparative Example 1; Figure 3 is the BJH pore size distribution diagram of Examples 1-3 and Comparative Example 1, from Figure 2 and Figure 3It can be seen that at a relative pressure of 0.1 to 0.9 (P / P0), the surface area of NPC-2 is the largest, and the hysteresis loop (Type IV isotherm) is more obvious, indicating that the interior of NPC-2 is a porous carbon material mainly composed of mesopores. The sharp increase in the adsorption amount indicates the presence of micropores at a lower relative pressure, and the presence of micropores can effectively increase the specific surface area of the material. An obvious loop appears at a relative pressure of 0.1 to 0.9, indicating that there are abundant mesopores. When the relative pressure is close to 1, an inclined line segment can be seen, indicating that there are larger pores in the sample. The pore size distribution ( Figure 3 ). A good pore structure can shorten the charge transfer distance and increase the transport of electrolyte ions, thereby improving the electrochemical performance of the material.
[0095] Figure 4 This is a test diagram of the actual capacity of supercapacitor products prepared using the carbon materials of Examples 1-3 and Comparative Examples 1-3; Figure 5 The test diagrams of the measured internal resistance of supercapacitor products prepared using the carbon materials of Examples 1-3 and Comparative Examples 1-3 are shown in Table 1. It can be seen from Table 1 that the nitrogen-doped material disclosed in the present invention has a high specific surface area. When used to prepare supercapacitors, the obtained supercapacitors have high capacity and low internal resistance, indicating that the nitrogen-doped material of the present invention can effectively increase the capacity of supercapacitors and reduce their internal resistance.
[0096] Finally, it should be noted that the above embodiments are used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a nitrogen-doped carbon material, characterized in that: The following steps are involved: Adding activated carbon and a nitrogen source into a solvent and mixing them evenly to obtain a first solution; placing the first solution in a reaction kettle and performing a hydrothermal reaction to obtain a first product; The first product and an activator are mixed and activated to obtain a nitrogen-doped carbon material; The nitrogen source is trans-1,2-cyclohexanediaminetetraacetic acid.
2. The method for preparing the nitrogen-doped carbon material according to claim 1, characterized in that: The mass ratio of the activated carbon to the nitrogen source is 1-4.
3. The method for preparing the nitrogen-doped carbon material according to claim 1, characterized in that: The mass ratio of the first product to the activator is 1-4.
4. The method for preparing the nitrogen-doped carbon material according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 160-200° C. and the time is 20-30 hours.
5. The method for preparing the nitrogen-doped carbon material according to claim 1, characterized in that: The activator is at least one of sodium hydroxide, potassium hydroxide, sodium oxide, potassium oxide, sodium carbonate, potassium carbonate, potassium bicarbonate, sodium bicarbonate, and calcium oxide; and / or the activation temperature is 600-800° C. and the activation time is 1.5-3 hours.
6. A nitrogen-doped carbon material, characterized in that The nitrogen-doped carbon material is prepared by the method for preparing the nitrogen-doped carbon material according to any one of claims 1 to 5.
7. An electrode sheet, characterized in that: The method comprises the nitrogen-doped carbon material according to claim 6, a conductive agent and a binder.
8. The electrode sheet according to claim 7, characterized in that: The conductive agent is at least one of conductive carbon black, carbon nanotubes, graphene, and vapor-grown carbon fibers.
9. The electrode sheet according to claim 7, characterized in that: The binder is at least one of N-methylpyrrolidone, sodium carboxymethyl cellulose and styrene-butadiene rubber.
10. A supercapacitor, characterized in that: An electrode sheet comprising any one of claims 7 to 9.
Citation Information
Cited By
Surface modification method of biomass supercapacitor activated carbon
CN120048661A
A method for surface modification of biomass supercapacitor activated carbon
CN120048661B
